Development of Local Wisdom-Based Science Learning E-Book Modules for Madrasah Aliyah Students - Aini, Marisdasatul; April Yanti, Fitri (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to produce a product in the form of a digital-based module intended for Madrasah Aliyah (MA) students. The research and development used in this study is the 4D model which stands for define, design, develop, and disseminate which is simplified to only a partial development stage. Data were collected through observation, interview, and documentation methods. The results showed an overview of the digital-based module development process, including analysis of learning needs, curriculum, students, subject matter, tasks, and formulating learning objectives. The design stage includes media selection, format, and initial design of digital-based modules. The development stage is only partially carried out and will involve making modules using the design that has been prepared. This digital-based module is hoped to help smooth the learning process, overcome obstacles in understanding science subjects, and allow students to learn independently at school and at home. In addition, the module also includes elements of local cultural preservation that can be an added value in education in the Madrasah Aliyah environment.